2006
DOI: 10.5558/tfc82253-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolving consumer preferences for residential decking materials

Abstract: Major changes are taking place in the residential decking market driven by concerns over wood preservatives and the resulting phase-out of chromated copper arsenic (CCA)-treated wood and recent entry into the marketplace by wood-plastic composites. Using conjoint analysis, this study explores consumer perceptions regarding residential decking materials over two time periods, 2000 and 2003. Type of material and lifetime were the most important decking attributes. Of lesser importance were annual maintenance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…This result agrees with another study that investigated playground manufacturers' perceptions of treated wood: health criteria are the most important considerations in material choice (Vlosky and Shupe 2005). Consumer perceptions regarding residential deck materials were investigated by Fell et al (2006). Based on two conjoint studies from 2000 and 2003, they concluded that consumers have become more negative towards treated wood and more positive to wood-plastic composites during the study period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result agrees with another study that investigated playground manufacturers' perceptions of treated wood: health criteria are the most important considerations in material choice (Vlosky and Shupe 2005). Consumer perceptions regarding residential deck materials were investigated by Fell et al (2006). Based on two conjoint studies from 2000 and 2003, they concluded that consumers have become more negative towards treated wood and more positive to wood-plastic composites during the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about the potential toxicity of chemically treated wood have led to attempts to phase out such products in several countries. As early as 2001, CCA-treated products were withdrawn from the Canadian market because of health concerns (Fell et al 2006), and a similar restriction on CCA-treated wood was imposed in 2003 by the Australian Pesticides and Veterinary Medicines Authority (2005aAuthority ( , 2005b (Jacobsen and Evans 2002). However, CCA is allowed to be used in industrial installations and structures in cases where durable materials are necessary for public safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Price and costs form the economic dimension of wooden properties. Price as an extrinsic cue is significant in predicting the quality attributes at the point of purchase (Steenkamp, 1989) and it was investigated in many studies (Bernard et al, 2018;Cai & Aguilar, 2013;Fell et al, 2006;Malá et al, 2019;Roos & Nyrud, 2008b;Teisl et al, 2002). Some studies also investigated the expensiveness of wooden material (Kuzman et al, 2012), costs (Strobel et al, 2017), financial demands of the construction (Moresová et al, 2019), and affordability (Spetic et al, 2007).…”
Section: Economic Dimensionmentioning
confidence: 99%
“…Price was discovered to be a significant factor influencing purchase decisions in some studies (e.g., Bernard et al, 2018;Strobel et al, 2017). However, when investigating residential wooden decking (Fell et al, 2006) and wood flooring , price was of lesser importance. In contrast to Fell et al (2006), in a study by Roos and Nyrud (2008b), price was seen as an important attribute of wooden deck materials.…”
Section: Economic Dimensionmentioning
confidence: 99%